Clinical utility of evolocumab in the management of hyperlipidemia: patient selection and follow-up - Dixon DL; Buckley LF; Trankle CR; Kadariya D; Abbate A (Dove Medical Press, 2017)
Dave L Dixon,1 Leo F Buckley,1 Cory R Trankle,2 Dinesh Kadariya,3 Antonio Abbate2 1Department of Pharmacotherapy and Outcomes Science, School of Pharmacy, 2Pauley Heart Center, 3Department of Internal Medicine, School of Medicine, Virginia Commonwealth University, Richmond, VA, USA Abstract: Inhibition of PCSK9 is a novel therapeutic strategy aimed at reducing low-density-lipoprotein cholesterol (LDL-C) and cardiovascular risk. Evolocumab is a fully humanized monoclonal antibody that inhibits PCSK9, an enzyme that binds to LDL receptors and prevents them from recycling to the hepatocyte surface. Clinical trials have demonstrated 50%–70% reductions in LDL-C with evolocumab when used in combination with statin therapy. The recent FOURIER trial demonstrated that evolocumab further reduces cardiovascular events, but not mortality, in high-risk patients already receiving statin therapy. Furthermore, evolocumab did not affect neurocognitive function and was not associated with antidrug-antibody production in over 60,000 patient-years of drug exposure. Appropriate candidates for evolocumab primarily are individuals at high cardiovascular risk, including those with familial hypercholesterolemia and/or established cardiovascular disease, who are already on statin therapy. At this time, the use of evolocumab monotherapy seems appropriate only for individuals deemed statin-intolerant despite attempting several statins. Consideration must be given toward patient willingness to self-inject evolocumab and issues concerning third-party coverage, given the current costs of evolocumab. Keywords: evolocumab, PCSK9, familial hypercholesterolemia, hyperlipidemia